From determination of the fugacity coefficients to estimation of hydrogen storage capacity: A convenient theoretical method. (14th September 2015) - Fu, Peng; Jia, Ran; Kong, Chui-Peng; Eglitis, Roberts I.; Zhang, Hong-Xing
Abstract: The equation of state (EOS) from virial expansion (VE) is used in this work to pave the way for determining the fugacity coefficients of the hydrogen fluid at arbitrary temperature and pressure. The fugacity coefficients from our VE method have more physical meanings than the empirical values. In this way, the hydrogen storage capacity of a novel material model can be estimated by using few density functional theory (DFT) calculations with the aid of a continuum model. The efficient continuum model can provide a more accurate estimation of the hydrogen storage capacity than the pure DFT calculations. Furthermore, the expensive grand canonical ensemble ( μNT ) simulations combining with the quantum mechanics methods (i.e., QM/MD- μNT ) are unnecessary within this method. The hydrogen fluid can be handled with our VE method at the temperature in the range of 160–773 K . The hydrogen storage capacity and the detailed thermodynamic information of a designed novel material can thereby be estimated by using this method with relatively high accuracy and low computing cost. As an example, the hydrogen storage capacities of the expanded bilayer graphene systems are presented. Our theoretical results agree with the experimental values very well. Graphical abstract: Highlights: A new equation of state is provided for the hydrogen fluid by using virial expansion. The full thermodynamic information is obtained by a series of DFT calculations. The hydrogen storage capacities of the expanded bilayer graphene systems are fixed. The hydrogen distribution profile in the system is presented.